(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is dedicated to the problem of the using of social dialects in the artistic speech and its influence on the culture of speech in particular. The role of social dialectizms is shown on the concrete examples in the texts of artistic style.